"Clipearium Teutonicorum" і "Zuricher Wappenrolle" та їх значення для вивчення Руської державної геральдики другої половини ХІІІ – початку ХІV ст. - Однороженко, О. (Спеціальні історичні дисципліни: питання теорії та методики, 2009)
Древнейшими западноевропейскими источниками, в которых присутствует информация по средневековой русинской (украинской) геральдике, являются: латиноязычная поэма „Clipearium Teutonicorum”, написанная немецким поэтом Конрадом фон Муре в 1260–1264 гг., а также иллюстрированный „Цюрихский гербовый свиток” начала ХІV в. Изучение данных памятников позволяет сделать вывод о наличии у их авторов реальной, однако неверно интерпретированной информации о древнем гербе Руского королевства. The most ancient West European sources that contain information on medieval Ruthenian (Ukrainian) heraldry are represented by the poem “Clipearium Teutonicorum” in Latin (1260–1264) written by a German poet Conrad von Mure and the illustrated Zürich heraldic scroll (of early XIV century). Investigation of the given monuments allows for the conclusion that their authors had factual, but misinterpreted information on the ancient coat of arms of the Ruthenian kingdom, which originated from the Romanovichs’ family coat of arms.